2022
DOI: 10.3390/f13071106
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Native Plants on Soil Remediation and Microbial Diversity in Jiulong Iron Tailings Area, Jiangxi

Abstract: Phytoremediation is an important solution to heavy metal pollution in soil. However, the impact of plants on microbial communities in contaminated soil also requires attention. Community-level physiological profiling (CLPP) based on the Biolog™ EcoPlate and high-throughput sequencing were used to study the soil microbial community in this article. The rhizosphere and bulk soil samples of six native species were collected from the iron mine tailings on Jiulong Mountain, Jiangxi Province. According to the averag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 68 publications
2
2
0
Order By: Relevance
“…Finally, and more importantly, the mulching treatment seems to favor the development of a higher number of metal-tolerant plant species, which in turn could enhance the phytoremediation of polluted soils. Our findings thus indicate that the mulching practice can be a suitable method for the remediation of heavy metal-polluted soils, confirming comparable observations in forest soils (Kiikkilä et al, 2001) and the high potential of native plants for phytoremediation (Nouri et al, 2011;Wang et al, 2022). All together these findings led us to partially support our fourth hypothesis.…”
Section: Discussionsupporting
confidence: 88%
“…Finally, and more importantly, the mulching treatment seems to favor the development of a higher number of metal-tolerant plant species, which in turn could enhance the phytoremediation of polluted soils. Our findings thus indicate that the mulching practice can be a suitable method for the remediation of heavy metal-polluted soils, confirming comparable observations in forest soils (Kiikkilä et al, 2001) and the high potential of native plants for phytoremediation (Nouri et al, 2011;Wang et al, 2022). All together these findings led us to partially support our fourth hypothesis.…”
Section: Discussionsupporting
confidence: 88%
“…The Cu content and pH in the bulk samples were similar to those reported by Ginocchio et al [19] for mine tailings in a closely located area within the same study area. The total contents of Fe and Cu, as well as the available Zn, were lower in the root zone compared to the bulk soil, which is similar to that reported in the literature when assessing Cu and Zn contents in the rhizosphere and bulk soil in mine tailings [12,13]. Contrarily, Ginocchio et al [59] reported higher Cu content beneath B. linearis shrubs in metal(loid) contaminated soils, attributing it to the physical retention of metal-enriched particles by the plant leaves.…”
Section: Discussionsupporting
confidence: 87%
“…Numerous studies have reported the presence of microbial groups in mine tailings, particularly in the rhizosphere of different plant species, which play roles in essential ecological processes [11]. Several studies have found a prevalence of Proteobacteria, Acidobacteria, Chloroflexi, Actinobacteria, and other taxa in various mine tailings, exhibiting advantageous traits for plant growth and development [11][12][13]. In this context, microbial communities act as pioneer colonizers, playing pivotal roles in elemental transformation, carbon and nitrogen fixation, and the enhancement of mineral soil fertility and plant growth [14].…”
Section: Introductionmentioning
confidence: 99%
“…Soil pollution occurs when pollutants accumulate in the soil, surpassing its self-purification ability [29]. Various forms of soil pollution arise from mineral resource development, including heavy metal pollution, organic matter pollution, solid waste pollution, and nuclear pollution.…”
Section: Soil Pollutionmentioning
confidence: 99%